Answer: -10, 10
Step-by-step explanation:
first lets add the two equations. add the x's, add the y's, add the constants on the right.
we get
0x - 1y = -10
so then divide --10 by -1 because we do the opposite operations to both sides
and we get y = 10
now substitute y = 10 into the first equation
-10x - 9(10) = 10
and then we get -10x - 90 = 10
now add 90 to both sides
-10x = 100
divide 100 by -10
x = -10
y = 10
checks out
EPIC. STAY EPIC AND AWESOME FRIEND.
Here’s the answer and each step I took to solve it. With the example I made on the side just continue to repeat that for each one to get the answers. You just replace that one number for the X to take the place for the next X value as you go down the table solving them.
Answer:
k = +4
Step-by-step explanation:
First you had to expanded form.
![-4(2a+5)=-8a-20](https://tex.z-dn.net/?f=-4%282a%2B5%29%3D-8a-20)
![9a-8a-20](https://tex.z-dn.net/?f=9a-8a-20)
Finally you can also add by similar to elements.
![9a-8a=a](https://tex.z-dn.net/?f=9a-8a%3Da)
![a-20](https://tex.z-dn.net/?f=a-20)
Final answer: ![\boxed{=a-20}](https://tex.z-dn.net/?f=%5Cboxed%7B%3Da-20%7D)
Hope this helps!
And thank you for posting your question at here on brainly, and have a great day.
-Charlie
I think the answer is (7x-3)(7x+3)